Factors affecting the production of H-2 by water splitting over a novel visible-light-driven photocatalyst GaFeO3 - Dhanasekaran, P.; Gupta, N. M. (International Journal of Hydrogen Energy, 2012)
A d(10) photocatalyst, GaFeO3 having a band gap of similar to 2.7 eV, exhibits significant activity for the overall splitting of water under visible light (>395 nm) irradiation, in the absence of sacrificial reagent or a noble metal co-catalyst. The doping of an anion led to considerable enhancement in activity, the S-doped catalysts displaying better activity compared to the samples containing nitrogen. Even though the H-2/O-2 yields were affected by preparation-dependent grain morphology, no direct relationship was observed between the photoactivity of a sample and its specific surface area. The techniques of HRTEM, SEM, XPS, Laser Raman, UV-visible and photoluminescence spectroscopy have enabled to demonstrate that, besides the grain morphology, certain lattice imperfections and microstructure may also play a crucial role in water splitting activity of a photocatalyst. The factors responsible for catalyst deactivation are examined. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: GaFeO3; hydrogen production; Microstructure; Photocatalyst; water splitting